Asymptotic Analysis of Lattice Boltzmann Outflow Treatments (Communications in Computational Physics, 2020)
We show the methodology and advantages of asymptotic analysis when appliedto lattice Boltzmann outflow treatments. On the one hand, one can analyze outflow algorithms formulated directly in terms of the lattice Boltzmann variables, like theextrapolation method, to find the induced outflow conditions in terms of the Navier-Stokesvariables. On the other hand, one can check the consistency and accuracy oflattice Boltzmann outflow treatments to given hydrodynamic outflow conditions likethe Neumann or average pressure condition. As example how the gained insight canbe used, we propose an improvement of the well known extrapolation method.